IMPACT OF YOUTUBE AS AN ACADEMIC LEARNING RESOURCE FOR STUDENTS: AN E-LEARNING THEORY PRACTICE - Phulpoto, Amanullah (APPS Publications, 2022)
The student habit of using the digital platforms can be used to compliment the traditional learning methods. Specifically, designed digital learning platform can support the learning with convenience of time, place, and pace. They can increase the engagement of students and produce higher learning outcomes with increased satisfaction and competence. This study aimed to explore the impact of YouTube as an online resource for academics and learning purpose of students. To fulfill the objective of the study, we conducted 12 semi-structured interviews, and employed thematic analysis procedure to analyze the data. Based on the framework of e-learning theory, we explored the impact of online YouTube based lectures on the academics of students. Moreover, in our empirical examination based on in-depth interviews, we found that the convenience provided by the platform and the expertise of content providers on YouTube help students solve their problems and meet their required goals of academics and learning. To conclude this study, the implications of these findings are discussed in detail.